#111 Design, synthesis, biological evaluation and in-silico study of imidazopyridine linked thiazolidinone as promise anticancer agents - Azhar, Iqbal Md; Asif, Husain; Sanjar, Alam (Journal of Pharmaceutical Chemistry, 2022)
Design, synthesis, biological evaluation, and in-silico study of imidazopyridine-linked thiazolidinedione promise anticancer agents. A series of imidazopyridine-linked thiazolidinedione rings (6a-h) were synthesized and tested for their antiproliferative activity against a panel of three human cancer cell lines viz., MCF7 (human breast cancer), A549 (human lung cancer), and DU145 (human prostate cancer). Two compounds 6f and 6h, exhibited remarkable results against all the three cell lines, but the compound 6h was found to be the most active against breast cancer cell lines. Amongst all the synthesized compounds, 6h displayed the highest antioxidant results. Further, potent compounds 6f, and 6h showed no signs of toxicity at a dose ranging from 50 to 500 mg/kg of body weight of animals. Biochemical parameters (SGOT and SGPT) of compound 6h have nearly matched the control in hepatotoxicity studies. Molecular docking & MM-GBSA dG bind studies agree with the outcome of in vitro anticancer and antioxidant activities. The most potent compound 6h, was found to have the highest docking score, binding energy, and ADME parameters, which are in the acceptable range. Thus, it could be concluded that 6h, an imidazopyridine derivative endowed with the thiazolidinedione ring system, has the potential to be developed as an anticancer agent.